Association polymers for modulated release of bioactive proteins. - Raiche, A.T.
The potential relevance for improving bone formation in and around tissue-engineered constructs. The objectives of this study were to investigate erosion and release of biologically active protein from CAP/PF-127 blends in an environment more representative of local growth factor delivery into a low clearance site. Within this study, effects of polymer blend ratio, sampling interval, and multilayering were examined with the ultimate goal of obtaining multiphasic release profiles over a period of several days.
Keywords: Association polymers; Biologically active protein; Local growth factor delivery; Modulated bioactive protein release; Tissue-engineered constructs